Insights from the international workshop on “Adapting agriculture to climate change and air pollution” - Evgenios Agathokleous; Lisa Emberson; Jie Pei; Kazuhiko Kobayashi; James D. Blande; Jo Cook; Chao Fang; Zhiyu Han; Hui Ju; Oliver Knopf; Tao Li; Bing Liu; et al. (Environmental Science and Pollution Research, 2024)

Assessing the spatio-temporal tropospheric ozone and drought impacts on leaf growth and grain yield of wheat across Europe through crop modeling and remote sensing data - Thuy Huu Nguyen; Giovanni Alessandro Cappelli; Lisa Emberson; Gonzalez Fernandez Ignacio; Anisoara Irimescu; Savian Francesco; Ginaldi Fabrizio; Nathan Booth; George Boldeanu; Victoria Bermejo; Sam Bland; Michael Frei; et al. (European Journal of Agronomy, 2024)

Impacts of tropospheric ozone and climate change on Mexico wheat production - Jose Rafael Guarin; Lisa Emberson; David Simpson; Ixchel M. Hernandez-Ochoa; Diane Rowland; Senthold Asseng (Climatic Change, 2019)

Closing the global ozone yield gap: Quantification and cobenefits for multistress tolerance - Gina Mills; Katrina Sharps; David Simpson; Håkan Pleijel; Michael Frei; Kent Burkey; Lisa Emberson; Johan Uddling; Malin Broberg; Zhaozhong Feng; Kazuhiko Kobayashi; Madhoolika Agrawal (Global Change Biology, 2018)
Increasing both crop productivity and the tolerance of crops to abiotic and biotic stresses is a major challenge for global food security in our rapidly changing climate. For the first time, we show how the spatial variation and severity of tropospheric ozone effects on yield compare with effects of other stresses on a global scale, and discuss mitigating actions against the negative effects of ozone. We show that the sensitivity to ozone declines in the order soybean > wheat > maize > rice, with genotypic variation in response being most pronounced for soybean and rice. Based on stomatal uptake, we estimate that ozone (mean of 2010–2012) reduces global yield annually by 12.4%, 7.1%, 4.4% and 6.1% for soybean, wheat, rice and maize, respectively (the “ozone yield gaps”), adding up to 227 Tg of lost yield. Our modelling shows that the highest ozone‐induced production losses for soybean are in North and South America whilst for wheat they are in India and China, for rice in parts of India, Bangladesh, China and Indonesia, and for maize in China and the United States. Crucially, we also show that the same areas are often also at risk of high losses from pests and diseases, heat stress and to a lesser extent aridity and nutrient stress. In a solution‐focussed analysis of these results, we provide a crop ideotype with tolerance of multiple stresses (including ozone) and describe how ozone effects could be included in crop breeding programmes. We also discuss altered crop management approaches that could be applied to reduce ozone impacts in the shorter term. Given the severity of ozone effects on staple food crops in areas of the world that are also challenged by other stresses, we recommend increased attention to the benefits that could be gained from addressing the ozone yield gap.

Ozone pollution will compromise efforts to increase global wheat production - Gina Mills; Katrina Sharps; David Simpson; Håkan Pleijel; Malin Broberg; Johan Uddling; Fernando Jaramillo; William J Davies; Frank Dentener; Maurits Van den Berg; Madhoolika Agrawal; Shahibhushan B. Agrawal; et al. (Global Change Biology, 2018)
Introduction of high‐performing crop cultivars and crop/soil water management practices that increase the stomatal uptake of carbon dioxide and photosynthesis will be instrumental in realizing the United Nations Sustainable Development Goal ( SDG ) of achieving food security. To date, however, global assessments of how to increase crop yield have failed to consider the negative effects of tropospheric ozone, a gaseous pollutant that enters the leaf stomatal pores of plants along with carbon dioxide, and is increasing in concentration globally, particularly in rapidly developing countries. Earlier studies have simply estimated that the largest effects are in the areas with the highest ozone concentrations. Using a modelling method that accounts for the effects of soil moisture deficit and meteorological factors on the stomatal uptake of ozone, we show for the first time that ozone impacts on wheat yield are particularly large in humid rain‐fed and irrigated areas of major wheat‐producing countries (e.g. United States, France, India, China and Russia). Averaged over 2010–2012, we estimate that ozone reduces wheat yields by a mean 9.9% in the northern hemisphere and 6.2% in the southern hemisphere, corresponding to some 85 Tg (million tonnes) of lost grain. Total production losses in developing countries receiving Official Development Assistance are 50% higher than those in developed countries, potentially reducing the possibility of achieving UN SDG 2. Crucially, our analysis shows that ozone could reduce the potential yield benefits of increasing irrigation usage in response to climate change because added irrigation increases the uptake and subsequent negative effects of the pollutant. We show that mitigation of air pollution in a changing climate could play a vital role in achieving the above‐mentioned UN SDG , while also contributing to other SDG s related to human health and well‐being, ecosystems and climate change.

A unifying explanation for variation in ozone sensitivity among woody plants - Zhaozhong Feng; Patrick Büker; Håkan Pleijel; Lisa Emberson; Per Erik Karlsson; Johan Uddling (Global Change Biology, 2018)
Tropospheric ozone is considered the most detrimental air pollutant for vegetation at the global scale, with negative consequences for both provisioning and climate regulating ecosystem services. In spite of recent developments in ozone exposure metrics, from a concentration‐based to a more physiologically relevant stomatal flux‐based index, large‐scale ozone risk assessment is still complicated by a large and unexplained variation in ozone sensitivity among tree species. Here, we explored whether the variation in ozone sensitivity among woody species can be linked to interspecific variation in leaf morphology. We found that ozone tolerance at the leaf level was closely linked to leaf dry mass per unit leaf area ( LMA ) and that whole‐tree biomass reductions were more strongly related to stomatal flux per unit leaf mass ( r 2 = 0.56) than to stomatal flux per unit leaf area ( r 2 = 0.42). Furthermore, the interspecific variation in slopes of ozone flux–response relationships was considerably lower when expressed on a leaf mass basis (coefficient of variation, CV = 36%) than when expressed on a leaf area basis ( CV = 66%), and relationships for broadleaf and needle‐leaf species converged when using the mass‐based index. These results show that much of the variation in ozone sensitivity among woody plants can be explained by interspecific variation in LMA and that large‐scale ozone impact assessment could be greatly improved by considering this well‐known and easily measured leaf trait.

Has the sensitivity of soybean cultivars to ozone pollution increased with time? An analysis of published dose–response data - Stephanie A. Osborne; Gina Mills; Felicity Hayes; Elizabeth A. Ainsworth; Patrick Büker; Lisa Emberson (Global Change Biology, 2016)
The rising trend in concentrations of ground‐level ozone (O 3 ) – a common air pollutant and phytotoxin – currently being experienced in some world regions represents a threat to agricultural yield. Soybean ( Glycine max (L.) Merr.) is an O 3 ‐sensitive crop species and is experiencing increasing global demand as a dietary protein source and constituent of livestock feed. In this study, we collate O 3 exposure‐yield data for 49 soybean cultivars, from 28 experimental studies published between 1982 and 2014, to produce an updated dose–response function for soybean. Different cultivars were seen to vary considerably in their sensitivity to O 3 , with estimated yield loss due to O 3 ranging from 13.3% for the least sensitive cultivar to 37.9% for the most sensitive, at a 7‐h mean O 3 concentration (M7) of 55 ppb – a level frequently observed in regions of the USA , India and China in recent years. The year of cultivar release, country of data collection and type of O 3 exposure used were all important explanatory variables in a multivariate regression model describing soybean yield response to O 3 . The data show that the O 3 sensitivity of soybean cultivars increased by an average of 32.5% between 1960 and 2000, suggesting that selective breeding strategies targeting high yield and high stomatal conductance may have inadvertently selected for greater O 3 sensitivity over time. Higher sensitivity was observed in data from India and China compared to the USA , although it is difficult to determine whether this effect is the result of differential cultivar physiology, or related to local environmental factors such as co‐occurring pollutants. Gaining further understanding of the underlying mechanisms that govern the sensitivity of soybean cultivars to O 3 will be important in shaping future strategies for breeding O 3 ‐tolerant cultivars.

Erratum to: Monitoring Nitrogen Dioxide Levels in Urban Areas in Rawalpindi, Pakistan - Sheikh Saeed Ahmad; Patrick Büker; Lisa Emberson; Rabia Shabbir (Water, Air, & Soil Pollution, 2012)

Monitoring Nitrogen Dioxide Levels in Urban Areas in Rawalpindi, Pakistan - Sheikh Saeed Ahmad; Patrick Biiker; Lisa Emberson; Rabia Shabbir (Water, Air, & Soil Pollution, 2011)